Implementasi Permainan Congklak untuk Meningkatkan Kemampuan Berhitung Siswa Sekolah Dasar (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to understand how the use of the game congklak can contribute to improving the numeracy skills of grade II elementary school students. Using a qualitative approach through a case study, this research involved students, teachers, and parents as resource persons to gain in-depth insights into the role of games in the math learning process. The research subjects were grade II students at SDS Islam Ulul Albab. The findings show that congklak can be an effective tool in helping students hone their numeracy skills. In addition to offering a fun way to learn, this game also helps train social skills, critical thinking, and strategy application. Based on observations and interviews, students were more active and enthusiastic when learning math through congklak, and were able to relate the subject matter to everyday life situations. Overall, congklak proved to be not only an interesting learning medium, but also has an important role in supporting students' cognitive and social development, so it has the potential to be an effective learning innovation at the primary school level.